Da Costa's syndrome or neurocirculatory asthenia. Issue 4 (October 1987) - Paul, O
Abstract : The syndrome variously called Da Costa's syndrome, effort syndrome, neurocirculatory asthenia, etc has been studied for more than 100 years by many distinguished physicians. Originally identified in men in wartime, it has been widely recognised as a common chronic condition in both sexes in civilian life. Although the symptoms may seem to appear after infections and various physical and psychological stresses, neurocirculatory asthenia is most often encountered as a familial disorder that is unrelated to these factors, although they may aggravate an existing tendency. Respiratory complaints (including breathlessness, with and without effort, and smothering sensations) are almost universal, and palpitation, chest discomfort, dizziness and faintness, and fatigue are common. The physical examination is normal. The aetiology is obscure but patients usually have a normal life span. Reassurance and measures to improve physical fitness are helpful.